Students’ Attitudes at UNRWA's University College for Educational Sciences in Palestine Toward Electronic Tests from their own Points of View - Marshood, Jamal Mohammad; Hamoda, Iman Mostafa; Mufreh, Duha Sami; Ayyash, Fatin Adel; Hamduni, Nujood Ayed (Journal of Educational and Psychological Sciences, 2023)
This study attempted to identify the students’ attitudes at UNRWA's University College for Educational Sciences in Palestine toward electronic tests from their own points of view. The researcher used a descriptive survey approach. A questionnaire was used as a tool of the study which consisted of (40) items. It was administered on a random sample of (114) students at UNRWA's University College for Educational Sciences in Ramallah governorate north of Palestine. The study found out that the students’ attitudes at UNRWA's University College for Educational Sciences in Palestine toward electronic tests got a t a total average of (2.62 out of 5), which meant it had a (moderate) degree, Meanwhile, at the fields level, the tests results field got the highest average (2.69) with a (moderate) degree, then the tests application field got an average of (2.64) with a (moderate) degree, then the tests nature field got an average of (2.55) with a (low) degree, There weren't statistically significant differences in the students’ attitudes toward electronic tests attributed to academic level variable, there weren't statistically significant differences attributed to gender variable in all fields except for )tests nature field( in favor of female category, and there were significant differences attributed to the specialization variable in favor of literary specialization category, In the light of the study results the research team presented a set of recommendations including: improving students’ awareness about the importance of electronic tests.
Keywords: Attitudes; Digital Learning; Educational Colleges